Can pillar suturing promote efficacy of adenotonsillectomy for pediatric osas? A prospective randomized controlled trial. (5th August 2013) - Chiu, Po‐Han; Ramar, Kannan; Chen, Kuang‐Chao; Tsai, Yih‐Jeng; Lin, Chia‐Mo; Chiang, Yuh‐Chyun; Lu, Chia‐Ying; Chiang, Rayleigh Ping‐Ying
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Pediatric obstructive sleep apnea syndrome (OSAS) is a common disorder with serious clinical implications if left untreated. The recommended initial treatment for pediatric patients with obstructive sleep apnea syndrome (OSAS) is adenotonsillectomy. However, recent reports have shown variable surgical results with adenotonsillectomy in the treatment of pediatric OSAS. Study Design Prospective, controlled study. Methods From April 2007 to August 2010, 24 participants were assigned alternatively to either adenotonsillectomy with pillar suturing (intervention group) or adenotonsillectomy alone (control group). Result The average improvement in apnea hypopnea index (AHI) was 42.6% in the control group and 79.9% in the intervention group (P=0.037). The success rate was 50% in the control group and 91.6% in the intervention group (P=0.034). Six patients (50%) in the intervention group achieved complete resolution of pediatric OSAS, as defined by an AHI <1/hour, compared to 2 patients (16.7%) in the control group (P=0.097). Conclusion Adenotonsillectomy with pillar suturing showed significant improvement in treating pediatric patients with OSAS compared to adenotonsillectomy alone. The procedure is simple and safe. Level of Evidence 4. Laryngoscope, 123:2574–2578, 2013